Influence of the Collector Channels on the Intraocular Pressure - Martínez Sánchez, G J; Escobar del Pozo, C; Villa Velázquez Mendoza, C I (Revista Mexicana de Ingenieria Biomedica, 2017)
The aim of the present study is to determine the influence of the position of the collecting channels on intraocular pressure and its contribution to the development of glaucoma. Numerical simulations were performed using the finite element method for two case studies. The first case is a simplified model of rectangular section that simulates the flow between two collecting channels. The second model describes flow throughout the Schlemm channel (CS), considering that it is a rigid ring of constant thickness, with four distributions of the collector channels. The pressure and velocity profiles are shown for both cases. In the simplified case, there are differences of 10 P a between the average pressures. The second model shows that the symmetric arrangement has a constant pressure distribution while the asymmetric cases have variations of 2 P a. The results confirm that the position of the collecting channels influences the intraocular pressure. This study shows that a transient analysis is needed to understand the whole process, considering the elastic properties of the CS as well as the variations of diameter of the collecting channels.